Peningkatan Pengetahuan Pendamping Lansia tentang Resiko Jatuh di Panti Sosial Tresna Werdha - Sondang Ratnauli Sianturi; Indriati Kusumaningsih; Fransiskus Bobby (Jurnal Abdimas Kesehatan (JAK), 2023)
The incidence of falls in the elderly increases in proportion to the increase in age in the elderly living in nursing homes. The problem that often occurs in the elderly who fall is due to instability when standing and walking so that they fall easily. At the Panti, the elderly is assisted by nurses and officers in each room. The ratio of the number of officers to elderly is 1:20. This makes the officers unable to pay attention to the elderly one by one and follow the elderly who are at risk of falling wherever their elderly go. For this reason, nurses and officers need to be given an explanation about the risk of falling in the elderly and the treatment that can be done. Activities carried out in the form of socialization regarding nursing care for the elderly who are at risk of filling out a fall risk assessment in the elderly using power point and a fall risk assessment sheet. This community service activity was attended by 15 elderly companions at PSTW. The results of this activity can increase the knowledge and abilities of elderly companions in determining the risk of falling in the elderly and how to handle them at PSTW